Spatiotemporal Adaptations‐Driven Dynamic Thra Activation Simulates a Skin Wound Healing Response - Zeming Li; Jiajun Tan; Chuqing Zhou; Siyi Zhou; Yuanli Ye; Xinzhu Li; Xinyu Shen; Tian Xie; Mengyue Wang; Jingwei Jiang; Yiping Zhao; Xiao Xiang; et al. (Advanced Science, 2025)
Abstract The evolutionary adaptation of skin repair drives sequential regenerative phases: epidermal proliferation rapidly restores barrier function, followed by dermal reconstruction through extracellular matrix remodeling to establish structural support, yet the molecular coordination of this spatiotemporal program remains unclear. While the endocrine system is crucial in modulating wound repair, the critical hormone receptors orchestrating tissue‐layer‐specific responses are unidentified. Here, bulk and single‐cell RNA sequencing, spatial transcriptomics, and in vivo/in vitro analyses in mouse models of hyperthyroidism and hypothyroidism, as well as wound and skin organoid models, are employed to identify the thyroid hormone receptor Thra as a key regulator of phase‐coupled regeneration through two distinct yet coordinated mechanisms. In the initial phase, epidermal Thra activates glutathione metabolism via Gamma‐Glutamylcyclotransferase (GGCT), driving keratin filament assembly to accelerate reepithelialization. In the subsequent phase, dermal Thra mediates the Serum Amyloid A3 (SAA3)‐Fibronectin 1 (FN1) interaction, establishing angiogenic niches essential for matrix maturation. Using the self‐assembled epidermis‐dermis dynamic skin organoid model, Thra's role in simulating the wound healing process is further confirmed. This study highlights the essential role of spatiotemporal adaptability in wound repair using Thra as a paradigm and provides insights for developing clinical strategies to enhance skin wound healing.